2014
DOI: 10.1117/1.jbo.19.11.115005
|View full text |Cite
|
Sign up to set email alerts
|

Film thickness frequency distribution of different vehicles determines sunscreen efficacy

Abstract: Sun protection factor (SPF) frequently differs between sunscreens containing the same composition of ultraviolet (UV) filters that primarily define sunscreen efficacy. We tested the hypothesis that the thickness frequency distribution of the sunscreen film is also responsible for and can explain the divergence in the measured SPF. For this, we developed a method to measure film thickness from the difference of topography before and after application of of sunscreen on pig ear epidermal membrane. The influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…In particular, the role of film thickness uniformity for sunscreen efficacy has been discussed extensively [33,34]. In recent studies, thickness frequency distribution of the sunscreen layer applied to the skin was measured and shown to be decisive for the performance of sunscreens [19]. The distribution of film thickness of equal amounts of applied sunscreen was found to vary widely depending on the structure with respect to the oil and water phase and the rheological properties of the sunscreen formulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the role of film thickness uniformity for sunscreen efficacy has been discussed extensively [33,34]. In recent studies, thickness frequency distribution of the sunscreen layer applied to the skin was measured and shown to be decisive for the performance of sunscreens [19]. The distribution of film thickness of equal amounts of applied sunscreen was found to vary widely depending on the structure with respect to the oil and water phase and the rheological properties of the sunscreen formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Since sun exposure evidently affects skin roughness, the question arises as to whether sunscreen application to the affected body sites should be adjusted to the altered surface topography. Recent reports have demonstrated that film thickness frequency distribution of applied sunscreen critically influences sun protection efficacy [19,20]. In those reports, the thickness of sunscreen was measured on an 8 × 8 mm 2 surface area of a skin substrate with a discretization step of 10 µm in both directions of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Organic (synthetic) and mineral UV filters pose relevant challenges related to their photo-stability in vitro and in vivo under UV irradiation [81,82], their homogeneous distribution onto the skin [83][84][85], and their capability to reach the viable layers of epidermis and obtain sufficient accumulation in the stratum corneum [86] while also avoiding their systemic penetration due to the widespread concerns on their toxicity [87]. A major role is played by vehicles, which undergo a continuous technological evolution in the highly competitive cosmetic world, moving from the traditional vaseline or oil-in-water (o/w) emulsion delivery systems.…”
Section: Formulation Of Sun Protective Cosmetics Based On Secondary Pmentioning
confidence: 99%
“…The influence of various experimental factors on in vitro SPF measurement has been investigated. The amount of product applied [7,8], the application procedure [9], the force applied during spreading [10,11], and the type of in vitro substrate have all been shown to impact the in vitro SPF value. Especially careful consideration has been given to the effect of the substrate for SPF measurement, especially its origin, either biological or synthetic [4,12,13,14], its roughness [15], and its surface properties, indicating the affinity of the sunscreen for the in vitro substrate [16].…”
Section: Introductionmentioning
confidence: 99%